Pengaruh Profesionalisme dan Disiplin Kerja terhadap Kinerja Guru di MTSN 1 Mojokerto - M.Nafi'us Sofyannas Thohirin; Nersiwad Nersiwad; Yuliasnita Verlandes (Jurnal Visi Manajemen, 2025)
This study aims to analyze the influence of professionalism and work discipline on teacher performance at MTsN 1 X. Professionalism is the attitude and ability of teachers in carrying out tasks in accordance with established competency standards, while work discipline reflects teacher compliance with the rules and responsibilities given. Teacher performance is seen as an important factor in determining the quality of education, so this study is relevant to support school quality improvement. This study uses a quantitative approach with a survey method. The study population was all 55 teachers at MTsN 1 X, who were also sampled using a saturated sampling technique. The research instrument was a Likert scale questionnaire that had passed validity and reliability tests. Data analysis was carried out by multiple linear regression using the latest version of the SPSS program. The statistical analysis was conducted to determine both partial and simultaneous effects of the independent variables on teacher performance. The results showed that professionalism partially had a significant effect on teacher performance with a significance value of 0.004. Work discipline also had a significant effect with a significance value of 0.003. The simultaneous test showed that professionalism and work discipline together had a significant effect on teacher performance with a significance value of 0.000. The coefficient of determination (R²) of 0.536 indicates that 53.6% of the variation in teacher performance can be explained by these two variables, while the remaining 46.4% is influenced by factors outside this study. These findings highlight the importance of maintaining professional standards and strict discipline to achieve optimal educational outcomes. The implication of this research is the need for schools to design targeted and sustainable teacher development programs to improve professionalism and work discipline. In conclusion, fostering professionalism and discipline is a strategic step to enhance teacher performance and educational quality.